Cyber-physical systems for next-generation networks - Rodrigues, Joel 1972-; Gawanmeh, Amjad 1975- (Advances in computer and electrical engineering (ACEE) book series, 2018)
"This book explores the notion of cyber-physical systems is to use recent computing, communication, and control methods to design and operate intelligent and autonomous systems using cutting edge technologies. It provides a comprehensive reference for recent and up-to-date technologies in communications, control, and networking issues in cyber-physical systems"...